Nanomolar inhibitor of the galectin-8 N-terminal domain binds via a non-canonical cation-π interaction - Edvin Purić; Mujtaba Hassan; Fredrik Sjövall; Tihomir Tomašič; Mojca Pevec; Jurij Lah; Jaume Adrover Forteza; Anders Sundin; Hakon Leffler; Ulf J. Nilsson; Derek T. Logan; Marko Anderluh (Communications Chemistry, 2025)
Abstract Galectin-8 is a tandem-repeat galectin consisting of two distinct carbohydrate recognition domains and is a potential drug target. We have developed a library of galectin-8N inhibitors that exhibit high nanomolar K d values as determined by a competitive fluorescence polarization assay. A detailed thermodynamic analysis of the binding of d-galactosides to galectin-8N by isothermal titration calorimetry reveals important differences in enthalpic and/or entropic contributions to binding. Contrary to expectations, the binding of 2-O-propargyl-d-galactoside was found to strongly increase the binding enthalpy, whereas the binding of 2-O-carboxymethylene-d-galactoside was surprisingly less enthalpy-driven. The results of our work suggest that the ethynyl group can successfully replace the carboxylate group when targeting the water-exposed guanidine moiety of a critical arginine residue. This results in only a minor loss of affinity and an adjusted enthalpic contribution to the overall binding due to non-canonical cation-π interactions, as evidenced by the obtained crystal structure of 2-O-propargyl-d-galactoside in complex with the N-terminal domain of galectin-8. Such an interaction has neither been identified nor discussed to date in a small-molecule ligand-protein complex.